Resistance to Artemisinin-based Combination Therapies in Uganda: An Impending Threat - Siegel, Elana Joelle (Consilience, 2011)
Plasmodium falciparum malaria is one of the most significant causes of morbidity and mortality in tropical Africa. Chloroquine phosphate emerged as the revolutionary drug of choice for the prevention and treatment of malaria, pushing the previously administered quinine to the sidelines. However, since the 1970s, sensitivity to chloroquine has been on the decline. In response to this, health professionals began to turn to a different drug: artemisinin-based combination therapies (ACT). ACT is now accepted by the World Health Organisation (WHO) as the most effective strategy to treat Plasmodium falciparum malaria, despite some initial misgivings (their long-term usefulness has yet to be determined). In this light, based on a few tentative studies conducted since 2003, the WHO has established an emerging, yet noticeable, trend in growing resistance to ACT drugs. Although, at this moment, there is no hard evidence of any ACT resistance within the Ugandan population, this paper will explore, through published and unpublished sources, and a baseline survey conducted in July 2008 by AMREF (African Medical and Research Foundation, an international medical organisation based in Kenya), how this resistance will soon emerge in Uganda, what the precipitating factors are, and through a careful evaluation of these causes, offer courses of action so as avoid the devastating consequences of ACT resistance.